Estimating the impact of energy efficiency on housing prices in Germany: Does regional disparity matter? - Lisa Taruttis; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2020)
The German government aims at a climate-neutral building stock by 2050 to reach the goals defined in the Climate Action Plan 2050. Increasing the energy efficiency of existing buildings is therefore a high priority. For this purpose, investments of private homeowners will play a major role since about 46.5% of the German dwellings are owner-occupied. To identify potential monetary benefits of investing in energetic retrofits, we investigate whether energy efficiency is reflected in property values of single-family houses in Germany. Thereby we examine possible heterogeneous effects among regions. With 455,413 individual observations on a 1km²-grid level for 2014 to 2018, this study adds to the literature 1) by examining the effect of energy efficiency on housing values for Germany on a more small-scale level and specifically investigating regional disparities in this context and 2) by estimating an energy efficiency value-to-cost ratio. Applying a hedonic analysis, we find a positive relationship between energy efficiency and asking prices. We also find evidence for regional disparities. Effects are significantly weaker in large cities compared to other urban areas, whereas the impact in rural areas is much stronger. Since property values are expected to decline in rural regions, homeowners could alleviate this development by increasing the energy efficiency of their dwellings.
Keywords: C31; Q40; R21; R31; 330; Energy efficiency; residential buildings; regional disparities; German housing market; hedonic analysis; housing value